Penyelidikan arkeometri di negeri Pahang - Ramli Zuliskandar, Nik Abdul Rahman Nik Hassan Shuhaimi, Sauman Yunus, Jusoh Adnan (N/A, 2014)
Penyelidikan arkeometri di negeri Pahang by Ramli Zuliskandar, Nik Abdul Rahman Nik Hassan Shuhaimi, Sauman Yunus, Jusoh Adnan,